The splenic marginal zone shapes the phenotype of leukemia B cells and facilitates their niche-specific retention and survival. (3rd June 2017) - Stache, Vanessa; Verlaat, Lydia; Gätjen, Marcel; Heinig, Kristina; Westermann, Jörg; Rehm, Armin; Höpken, Uta E.
ABSTRACT: Microenvironmental regulation in lymphoid tissues is essential for the development of chronic lymphocytic leukemia. We identified cellular and molecular factors provided by the splenic marginal zone (MZ), which alter the migratory and adhesive behavior of leukemic cells. We used the Cxcr5 −/− Eµ-Tcl1 leukemia mouse model, in which tumor cells are excluded from B cell follicles and instead accumulate within the MZ. Genes involved in MZ B cell development and genes encoding for adhesion molecules were upregulated in MZ-localized Cxcr5 −/− Eµ-Tcl1 cells. Likewise, surface expression of the adhesion and homing molecules, CD49d/VLA-4 and CXCR7, and of NOTCH2 was increased. In vitro, exposing Eµ-Tcl1 cells or human CLL cells to niche-specific stimuli, like B cell receptor- or Toll-like receptor ligands, caused surface expression of these molecules characteristic for a follicular or MZ-like microenvironment, respectively. In vivo, inhibition of VLA-4-mediated adhesion and CXCL13-mediated follicular homing displaced leukemic cells not only from the follicle, but also from the MZ and reduced leukemia progression. We conclude that MZ-specific factors shape the phenotype of leukemic cells and facilitate their niche-specific retention. This strong microenvironmental influence gains pathogenic significance independent from tumor-specific genetic aberrations.